ABOUT GROUPS OF ANALOGUE DOCTORAL MEANINGS APPLIED BY ALISHER NAVAI - Jahonova Nargiza Yunusovna (International Journal of Innovations in Engineering Research and Technology, 2023)
This article is dedicated to literary scholars dealing with the work of Alisher Navoi, and the similarities found in the writer’s work and their lexical and spiritual groups are discussed. An attempt was made to reveal the groups of similes in the writer’s work, their place in the Uzbek language and literature, culture, and social, artistic and aesthetic thinking of the world.